Ensiling characteristics, in vitro digestibility and bacterial community structure of mulberry leaf silage with or without the addition of cellulase, protease, and starch - Zhao, Guoqiang; Wu, Hao; Li, Yangyuan; Huang, Zhiyi; He, Jiajun; Xie, Xiangxue (Frontiers in Plant Science, 2025)
ObjectiveThis study aimed to investigate the effects of cellulase, protease, and starch on the fermentation quality, in vitro digestibility, and microbial community of mulberry leaf silage after 30d of ensiling.MethodsMulberry leaves (376 g/kg dry matter (DM)) were ensiled with four experimental treatments: i) CON, no additives; ii) CEL, added cellulase (120 U/g fresh matter [FM]); iii) CPR, added cellulase (120 U/g FM) and protease (50 U/g FM); and iv) CPS, added cellulase (120 U/g FM), protease (50 U/g FM), and starch (2% FM).ResultsAll treatments with additives improved fermentation quality, showing higher DM (353 ~ 378 vs. 341 g/kg DM), lactic acid (LA) content (51.6 ~ 64.6 vs. 40.2 g/kg DM), lactic acid bacteria (LAB) counts (7.63 ~ 7.73 vs. 7.49 log10 CFU /g of FM), along with lower pH values (4.29 ~ 4.60 vs. 5.09), and DM losses (124 ~ 130 vs. 134 g/kg DM) compared to the CON group. All the additive treated groups showed higher in vitro digestibility of DM (698 ~ 720 vs. 618 g/kg DM), in vitro digestibility of NDF (395 ~ 412 vs. 336 g/kg DM), and ADF (277 ~ 298 vs. 232 g/kg DM) than CON. Among all the groups, the CPS group exhibited the highest DM content (378 g/kg DM), LA content (64.6 g/kg DM) and LAB counts (7.73 log10 CFU /g of FM), with the lowest pH value (4.29) and DM losses (124 g/kg DM). Additionally, the additive treatments increased abundance of bacteria like Firmicutes and Enteroccocus, while reducing Proteobacteria abundance, and resulted in lower diversity and richness of the microbial community. Specifically, CPR and CPS silages showed increased Pediococcus and decreased Enterobacter compared to CON and CEL, and CPS silage had a relatively high abundance of favorable Bacteroidota. Furthermore, the CPS silage exhibited upregulated genetic functions, energy and lipid metabolism, as well as metabolism of cofactors and vitamins compared to the other groups.ConclusionThe combined application of cellulase, protease, and starch effectively improved the fermentation quality, in vitro digestibility, and microbial community of mulberry leaf silage over the 30-day ensiling period.